2014
DOI: 10.1097/ta.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid administration to pediatric trauma patients in a combat setting

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 23 publications
1
78
0
3
Order By: Relevance
“…7,8 These studies also contrast with the retrospective MATTERS study, which showed a survival benefit in severely injured military casualties treated with TXA. 20 In addition, two studies, one a prospective cohort study of civilian trauma patients 21 and the other a retrospective study in pediatric trauma patients, 22 showed TXA to be beneficial in hemorrhagic shock patients.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 These studies also contrast with the retrospective MATTERS study, which showed a survival benefit in severely injured military casualties treated with TXA. 20 In addition, two studies, one a prospective cohort study of civilian trauma patients 21 and the other a retrospective study in pediatric trauma patients, 22 showed TXA to be beneficial in hemorrhagic shock patients.…”
Section: Discussionmentioning
confidence: 98%
“…17 The CRASH-2 (Clinical Randomization of an Antifibrinolytic in Significant Haemorrhage-2) randomized controlled trial, which enrolled 20,211 adults with hemorrhagic trauma in 40 countries, demonstrated that TXA decreased mortality at 28 days compared to placebo (risk of death 0.91; 95%CI 0.85 to 0.97) and had an even greater impact on death due to hemorrhage (risk of death due to hemorrhage OR, 95% CI). 17 Based on the results of this adult trial and that of an observational pediatric study that also demonstrated improved survival associated with TXA use, 9 some experts have advocated for the use of TXA in injured children with potentially hemorrhagic injuries. 10 In the UK, the Royal College of Paediatrics and Child Health and the Neonatal and Paediatric Pharmacists Group issued an evidence statement recommending a pragmatic dosage of TXA for children with major trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A single retrospective cohort study of 766 injured children in Afghanistan reported that TXA was only used in 10% of pediatric trauma admissions, although its administration was independently associated with a 27% reduction in mortality (p=0.03). 9 …”
Section: Introductionmentioning
confidence: 99%
“…5 A recent evaluation of the use of TXA among pediatric trauma patients in a combat setting (PED-TRAX) identified an independent association between the administration of TXA and decreased mortality without safety or medicationrelated complications. 17 The ability to translate these adult and preliminary findings broadly to pediatric patients may have important implications for the future of pediatric trauma care. There are several limitations to our study.…”
Section: Article In Pressmentioning
confidence: 99%